Combined chemical and thermal sintering for high conductivity inkjet-printed silver nanoink on flexible substrates - Ivanišević, Irena (Array, 2019)
Electrical conductivity is a key factor in measuring performance of printed electronics, but the conductivity of inkjet-printed silver nanoinks greatly depends on post-fabrication sintering. In this work, two different conductive silver nanoinks, in which the silver nanoparticles were stabilized by two different capping agents – Poly(acrylic acid) (PAA) and Poly(methacrylic acid) (PMA) – were synthesized. The inks were inkjet-printed on flexible PET substrates, coated with an additional polycation layer, which facilitated chemical sintering. The printed features were then exposed to moderately elevated temperatures to evaluate the effect of combined chemical and thermal sintering. Both inks produced conductive features at room temperature, and the conductivity increased with both temperature and duration of sintering. At temperatures above 100 °C, the choice of capping agent had no pronounced effect on conductivity, which approached very high values of 50 % of bulk silver in all cases. The lowest resistivity (2.24 μΩ cm) was obtained after sintering at 120 °C for 180 min. By combining chemical and conventional thermal sintering, we have produced remarkably conductive silver electrodes on flexible substrates, while using low-cost and simple processes.